Effective interface engineering for phonon manipulation in an Al/ErAs/GaAs system. (November 2022) - Pan, Jiahui; Fan, Xing; Zhang, Kedong; Geng, Zhiming; Yao, Jinshan; Deng, Yu; Zhou, Jian; Yan, Xue-Jun; Lu, Ming-Hui; Lu, Hong; Chen, Yan-Feng
Abstract: Interface, an effective means of phonon manipulation, is an important concept to be clarified in the study of interfacial thermal transport. In this work, we have used semi-metallic ErAs in a variety of forms to modify the morphology of an Al/GaAs interface so is the interfacial thermal resistance. Using the time-domain thermoreflectance technique, we have measured the interfacial thermal conductance and demonstrated effective phonon manipulation in this Al/ErAs/GaAs system. As the ErAs thickness changes, we have observed clear transitions of phonon behaviors from ballistic to diffusive. The ErAs thickness for ballistic transport is determined to be up to 30 nm in this material system. The thickness dependent thermal conductivity of ErAs is also determined and the electron contribution is estimated to be about 50–60% in the total thermal conductivity. Graphical abstract: Image 1 Highlights: Semi-metallic ErAs was used to tune the interfacial thermal resistance of Al/GaAs. Effective phonon manipulation by interface engineering is demonstrated in this Al/ErAs/GaAs system. A critical ErAs thickness of 30 nm marks the phonon transport transition from ballistic to diffusive.